2018
DOI: 10.1371/journal.pone.0200213
|View full text |Cite
|
Sign up to set email alerts
|

Protection induced by a Francisella tularensis subunit vaccine delivered by glucan particles

Abstract: Francisella tularensis is an intracellular pathogen causing the disease tularemia, and an organism of concern to biodefence. There is no licensed vaccine available. Subunit approaches have failed to induce protection, which requires both humoral and cellular immune memory responses, and have been hampered by a lack of understanding as to which antigens are immunoprotective. We undertook a preliminary in silico analysis to identify candidate protein antigens. These antigens were then recombinantly expressed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Several subunit and live attenuated vaccines have been tested. Whelan et al (2018) recently showed that a subunit vaccine, comprising Francisella LPS and the FTT_0814 protein delivered within glucan particles, was able to induce protection against Ft Schu S4 challenge in the Fischer 344 rat model. However, other subunit vaccines based on LPS, carbohydrates, and other surface antigens were unable to provide complete protection, and it is thought that both humoral and cell-mediated immune responses are required to achieve protective immunity (Pechous et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several subunit and live attenuated vaccines have been tested. Whelan et al (2018) recently showed that a subunit vaccine, comprising Francisella LPS and the FTT_0814 protein delivered within glucan particles, was able to induce protection against Ft Schu S4 challenge in the Fischer 344 rat model. However, other subunit vaccines based on LPS, carbohydrates, and other surface antigens were unable to provide complete protection, and it is thought that both humoral and cell-mediated immune responses are required to achieve protective immunity (Pechous et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies confirm the release of CD4+ T cells and IFN γ cells to protect from the infections. Thus, suggesting the importance of identification of T-cell epitopes epitope-based vaccine approach has been reported for Francisella tularensis (Whelan et al 2018), Haemophilus influenzae (Zahroh et al 2016), Dengue virus (Chakraborty et al 2010), Human coronaviruses (Oany et al 2014), Chikungunya virus (Islam et al 2012), and Ebola (Srivastava et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Subunit vaccines with GPs encasing soluble alkaline extracts of Cryptococcus neoformans acapsular strain (cap59) protected mice challenged with lethal doses of highly virulent C. neoformans (60% survival) by inducing an antigen‐specific CD4 + T cell response (positive for IFN‐γ, IL‐17a) that reduced the fungal colony‐forming units (CFU) more than 100‐fold from the initial challenge dose . A similar strategy of vaccinating mice with GP encapsulating antigens proved efficacious against Histoplasma capsulatum , F. tularensis , Blastomyces dermatitidis and C. posadasii . The versatility of using GPs vaccines against microbial pathogens is summarized in Table .…”
Section: Gps With Non‐covalently Encapsulated Antigens For Vaccine Dementioning
confidence: 99%
“…We hypothesized that subunit vaccines are most attractive due to their defined nature and thus good safety profiles, but that we needed to deliver promising candidate antigens in a manner that induced both humoral and cellular immune responses to achieve protection, as only a balanced humoral and cellular immune memory response, supported by innate immune mechanisms, protects against tularaemia (reviewed by Roberts et al and Krokova et al ). We therefore decided to employ the GP vaccine delivery platform described above to address this challenge . This work is summarized below.…”
Section: Tularaemia: a Challenge For Vaccinologymentioning
confidence: 99%